Dakwah dalam Mewujudkan Interaksi dan Kerukunan Antar Umat Beragama Di Palopo Sulawesi Selatan - Masmudin, Masmudin (Fakultas Dakwah IAIN Purwokerto, 2018)
Da’wah is carried out to spread the teachings of religion where humans as human beings choose religion according to their respective beliefs, but the reality that is seen now is that religion becomes a commodity and even a source of conflict. a lot of misunderstandings between religious people so that the harmony between religious groups can be realized well. Da’wah is done to increase understanding for followers of religion and society, this is also done as a preventive trap from the inclusion of an incorrect understanding of religion. Missionary mission is carried out to explain the teachings of the religion which he believes with the aim that other people can understand the teachings of religion through preaching delivered and can be implemented in daily life. Palopo is one of the administrative cities in the region of South Sulawesi, and the people of Palopo are Muslims, Christians, Catholics, Protestants, Hindus, Buddhists, and Confucians. The difference in religious beliefs in the Palopo community is expected to provide positive interactions so that there are harmonious communication and interaction as well as harmony between the religious community and their followers.